Financial Technology Peer-to-Peer Lending Accountability for Default Events in Channeling Financing Cooperation with Digital Banks - Tegar Aji Payoga; Pujiyono Suwadi (Green Publisher, 2024)
Digital disruption has transformed the banking sector from conventional to digital services, driving new forms of collaboration between digital banks and fintech lending companies. This study aims to analyze the legal aspects and identify the risks involved in channeling financing schemes within these partnerships. With fintech lending dominating Indonesia’s fintech ecosystem, digital banks face heightened credit risks due to the unpredictable nature of non-performing loans in fintech. The legal framework governing these collaborations is built on a channeling financing cooperation agreement, highlighting power dynamics and responsibilities between the parties. The findings emphasize the importance of clear and robust regulations to provide legal certainty and protection in such partnerships.